MATHEMATICS
COLLEGE

Answer: Since we know that the population mean is 5.67, we also know that the mean of sample means is also 5.67 because they are equal.

HIGH SCHOOL

A cartoon lasts 18 minutes. How many seconds is the cartoon?

There are 60 secs in every minute. 60 x 18 = 1080 seconds

18 times 60-

1 minute= 60 seconds

1080 seconds

1 minute= 60 seconds

1080 seconds

MIDDLE SCHOOL

Solve for x. 4(3x + 12) = −36 Enter your answer in the box.

Eqution is formed of two expressions. The value of x in the given equation 4(3x + 12) = -36 is -7.

What is an equation?An equation is formed when two expressions are equated together with the help of an equal sign.

As the equation 4(3x + 12) = −36, is given to us, and we need to find the value of x, therefore, the solution of the problem can be written as,

Hence, the value of x in the given equation 4(3x + 12) = -36 is -7.

Learn more about Equation:

brainly.com/question/2263981

To start I would distribute the 4 to the numbers in the parenthesis. So your equation would then look like 12x+48=-36. Then you need to subtract the 48 from both sides making your equation 12x=-84. Then divide both sides by 12 giving your answer:

x=-7.

To check it you can put the -7 in for x in your original equation. Which, when you do that it is -36=-36.

Hope this helped!

x=-7.

To check it you can put the -7 in for x in your original equation. Which, when you do that it is -36=-36.

Hope this helped!

COLLEGE

-5/3/10 as a improper fraction

What is your question

MIDDLE SCHOOL

Im on this question and its Marcella divided 40.8g of paint among 8 containers. how much paint is in each container? i got 40.8/8=5.1 but i need that as a fraction.. anyone got a answer?

Your answer is right in a fraction form you would put 5.1 over 1 and times both the denominator and numerator by a 100 it would give you 510 over 100, you divide this by 10 and it would give you 51 over 10 and this will be in the simplest form

HIGH SCHOOL

Solve for x. 3(3x - 1) + 2(3 - x) = 0

The equation given in the question is

3(3x - 1) + 2(3 - x) = 0

9x - 3 + 6 - 3x = 0

6x + 3 = 0

6x = - 3

x = - (3/6)

= - (1/2)

So the value of x as has been determined above is -1/2. I hope the procedure is clear enough for you to understand.You can always use this method for solving problems that are similar in type without requiring any help from outside.

3(3x - 1) + 2(3 - x) = 0

9x - 3 + 6 - 3x = 0

6x + 3 = 0

6x = - 3

x = - (3/6)

= - (1/2)

So the value of x as has been determined above is -1/2. I hope the procedure is clear enough for you to understand.You can always use this method for solving problems that are similar in type without requiring any help from outside.

MIDDLE SCHOOL

If x=2, which inequality is true?

Answer:

x=2

Step-by-step explanation:

Answer:

Step-by-step explanation:

Pls show an example?

MIDDLE SCHOOL

The graph of f(x) = 0.4x is replaced by the graph of g(x) = 0.4x + k. If g(x) is obtained by shifting f(x) up by 4 units, then what is the value of k? k = 4 k = −4 k equals negative one fourth k equals one fourth

Answer:

The value of k=4

Step-by-step explanation:

we have

f(x)=0.4x

This function represent a linear direct variation (The line passes through the origin)

we know that

If f(x) is shifting up by 4 units

then

The y-intercept of the function will be the point (0,4)

therefore

The function g(x) will be -----> g(x)=0.4x+4 (equation of the line into slope intercept form)

The rule of the translation

f(x) --------> g(x)

(x,y) -------> (x,y+4)

The translation is 4 units up

therefore

The value of k=4

Answer:

k = 4

Step-by-step explanation:

Remember if a graph is displaced by a certain number of units, you have to add that number to the equation of the line, in this case the equation was f(x)=0.4x, this means that y will be 0.4 of whatever value is given to x, now if the graph moves up, 4 units, this means that to that equation we have added 4 positive units, so when x is 0, the graph will be in (0,4) and thats the origin of the graph, in the first graph, the origin would be (0,0) since when x=0 y= 0 as well.

HIGH SCHOOL

Monica gets on an elevator in a skyscraper. The elevator starts to move at a rate of -20ft/s. After 6 seconds on the elevator, Monica is 350 ft from the ground floor building. 1) The rate of the elevator is negative. What does this mean in the situation? What value in the slope-intercept form of an equation does the rate represent?

2) How many feet was Monica above the ground when she got on the elevator? Show work

3) What value in the slope-intercept form does your answer to part a represent?

Show all work

1)

negative rate, means is decreasing, rather than increasing, meaning is going to 0 or beyond, instead of going up.

well, the slope is the rate of change of "y" in respect to "x", y = mx + b

2)

well... let's see, the elevator is going down by 20ft/s, so every second is 20feet, now, she was in the elevator for 6seconds, that means 6 * 20, 120feet, however, 6secs later, she's 350 "above" the ground, she's not really on the ground yet.

so, she went on the elevator down for 120feet and was above the ground 350feet, she was up high 120 + 350 feet from the ground.

3)

hmm not sure what's asking

negative rate, means is decreasing, rather than increasing, meaning is going to 0 or beyond, instead of going up.

well, the slope is the rate of change of "y" in respect to "x", y = mx + b

2)

well... let's see, the elevator is going down by 20ft/s, so every second is 20feet, now, she was in the elevator for 6seconds, that means 6 * 20, 120feet, however, 6secs later, she's 350 "above" the ground, she's not really on the ground yet.

so, she went on the elevator down for 120feet and was above the ground 350feet, she was up high 120 + 350 feet from the ground.

3)

hmm not sure what's asking

HIGH SCHOOL

A system of equations is shown below: x + y = 3

2x − y = 6

The x-coordinate of the solution to this system of equations is _____.

X+y=3

Subtract x from both sides

y=-x+3

Substitute

2x--x+3=6

2x+x+3=6

3x+3=6

Subtract 3 from both sides

3x=3

Divide both sides by 3

x=1

Subtract x from both sides

y=-x+3

Substitute

2x--x+3=6

2x+x+3=6

3x+3=6

Subtract 3 from both sides

3x=3

Divide both sides by 3

x=1